MutSpliceDB: A database of splice sites variants with RNA‐seq based evidence on effects on splicing. Issue 4 (1st March 2021) - Palmisano, Alida; Vural, Suleyman; Zhao, Yingdong; Sonkin, Dmitriy
Abstract: Splice site variants may lead to transcript alterations, causing exons inclusion, exclusion, truncation, or intron retention. Interpreting the consequences of a specific splice site variant is not straightforward, especially if the variant is located outside of the canonical splice sites. We developed MutSpliceDB: https://brb.nci.nih.gov/splicing, a public resource to facilitate the interpretation of splice sites variants effects on splicing based on manually reviewed RNA‐seq BAM files from samples with splice site variants.